Facebook in the Trap of Censorship - Simeonova, Lora (Media and Language, 2018)
Facebook is trapped by its own acceleration. The largest social network, despite of denying it, has transformed into media platform which has no editor-in-chief. Therefore Facebook is hesitating between absurd censorship, on one hand, and its complete weakness regarding propaganda, fake news and troll’s campaigns, on the other. The social network gave birth to a new horror genre – “Live Death” – a reality show which the algorithms so far are incapable to control.
Keywords: censorship; social networks; propaganda; fake news; trolls